SINERGI KESIAPAN KERJA: SOSIALISASI PENGEMBANGAN KARIR BERBASIS KOMPETENSI DAN STRATEGI LITERASI KEUANGAN PRIBADI BAGI SISWA DI SMK MANDIRI 2 BALARAJA - Wulan Aulia Sapitri; Fitri Okta Riani; Arafah Arafah; Dina Novita Sari; Mellyana Aisya (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
A The work readiness of vocational graduates is a strategic issue amidst increasingly tight industrial competition. This Community Service (PKM) aims to improve work readiness through socialization on competency-based career development and personal financial literacy strategies for students at SMK Mandiri 2 Balaraja. The program penetration focuses on two empirical urgencies: students' limited understanding of career planning (soft and hard skills) and the high level of consumptive behavior unmatched by adequate financial literacy. The implementation utilized a systematic approach through three main stages: problem identification, education (interactive lectures and simulations), and empirical evaluation using pre-test and post-test instruments. A total of 35 participants were involved, with 25 respondents measured for effectiveness. The results indicated a significant parameter increase; knowledge regarding competency-based career development increased by 32% (from an average score of 62 to 94), the skill in arranging financial budgets increased by 27%, and a highly positive attitude was formed with an average score of 4.6 out of a 5 scale towards personal financial management awareness. In conclusion, early educational intervention has proven effective in bridging the gap in work competencies of vocational graduates while building fundamental financial independence.